Volatile gas scavenging in the paediatric intensive care unit: Occupational health and safety assessment - Katherine Reise; Jason Macartney; Richard La; Angela Jerath; Marat Slessarev; Brian H. Cuthbertson; Saptharishi Lalgudi Ganesan; Nicole K. McKinnon (Canadian Journal of Respiratory Therapy)
# Introduction